2009
DOI: 10.1007/s11745-009-3311-9
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Both Polyunsaturated Fatty Acid Biosynthetic Pathways in Schizochytrium sp.

Abstract: Schizochytrium produces long chain polyunsaturated fatty acids (PUFAs) via a PUFA synthase. Targeted mutagenesis of one gene of this synthase was conducted to confirm PUFA synthase function and determine its metabolic necessity. The resulting mutants were auxotrophic and required supplementation with PUFAs. In vivo labeling experiments with radioactive fatty acids demonstrated the presence of several elongase and desaturase activities associated with the standard pathway of PUFA synthesis. However, this system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(83 citation statements)
references
References 25 publications
4
78
0
Order By: Relevance
“…ATCC 20888 failed to reveal the expected number and types of elongase and desaturase, whereas PKS-homologous sequences were well represented. In contrast, a recent study using radiolabeled precursor fatty acids revealed that this strain had several elongase and desaturase activities associated with the elongation/ desaturation pathway, but the pathway was incomplete for the synthesis of PUFAs from C16 or C18 fatty acids 21 . Although it is unclear why Δ5-elongase or Δ4-desaturase was not amplified from the genus Aurantiochytrium in this study, it could be due to a mismatch of the degenerated primers used or low sequence homology of these genes in Aurantiochytrium.…”
Section: Discussionmentioning
confidence: 63%
“…ATCC 20888 failed to reveal the expected number and types of elongase and desaturase, whereas PKS-homologous sequences were well represented. In contrast, a recent study using radiolabeled precursor fatty acids revealed that this strain had several elongase and desaturase activities associated with the elongation/ desaturation pathway, but the pathway was incomplete for the synthesis of PUFAs from C16 or C18 fatty acids 21 . Although it is unclear why Δ5-elongase or Δ4-desaturase was not amplified from the genus Aurantiochytrium in this study, it could be due to a mismatch of the degenerated primers used or low sequence homology of these genes in Aurantiochytrium.…”
Section: Discussionmentioning
confidence: 63%
“…which is particularly interesting as it also has two alternative pathways for DHA synthesis and contains a polyketide pathway not requiring aerobic desaturases (33,34). However, as expected, the phylogenetic analysis showed that the S. canaliculatus Δ4 Fad was more closely related to other vertebrate Δ6 and Δ5 Fads than the algal and protozoan Δ4 desaturases (35).…”
Section: Discussionmentioning
confidence: 64%
“…Primary production of in Schizochytrium is via a PUFA synthase (Metz et al, 2001), a series of 3 genes similar to those found in LC-PUFAproducing marine bacteria (Yazawa, 1996;Morita et al, 2000). In addition, a series of aerobic PUFA desaturase and elongase genes are also present in Schizochytrium (Lippmeier et al, 2009). …”
Section: 23microalgaementioning
confidence: 90%
“…are particularly interesting as they appear to have two alternative pathways for n-3 LC-PUFA biosynthesis (Lippmeier et al, 2009). Primary production of in Schizochytrium is via a PUFA synthase (Metz et al, 2001), a series of 3 genes similar to those found in LC-PUFAproducing marine bacteria (Yazawa, 1996;Morita et al, 2000).…”
Section: 23microalgaementioning
confidence: 99%